VLA and Effelsberg observations of the interstellar medium around the runaway star WR 124 - Cichowolski, Silvina (2008)
Aims: We present very large array (VLA) and Effelsberg radio continuum and 21 cm Hi line observations of the interstellar medium (ISM) surrounding the runaway star WR 124 and the nebula M 1-67. The HI data have been used to investigate the effects that a star with a strong stellar wind and a high peculiar velocity has on the ISM. Methods: The VLA 21 cm HI observations were combined with single-dish Effelsberg observations to produce a series of HI images sensitive to all angular scales from the VLA resolution limit (∼46") up to the primary field of individual VLA antennae (FWHM = 36'). MSX and IRIS images were used to analyze the infrared emission around the star. Because the star is highly supersonic with respect to its local ISM, the observed HI distribution around the star is interpreted in terms of a simple bow shock model. Results: The analysis of the HI data reveals the presence of a cavity centered on the star at an LSR velocity of ∼60 km s-1, consistent with a distance estimate of 5 kpc for WR124. A second HI cavity is observed located 10' to the north of the stellar position, consistent with the direction of motion of WR 124. The VLA continuum image at 8.5 GHz shows a remarkable resemblance to the optical images. All available radio continuum data suggest a purely thermal spectrum for the nebula. The MSX and IRIS infrared data show a changing morphology with wavelength. The dust temperature deduced from the infrared luminosities is in agreement with previous observations of bow shocks.